1992
DOI: 10.1007/bf02635812
|View full text |Cite
|
Sign up to set email alerts
|

Alkylphenol ethoxylates in the environment

Abstract: A comprehensive monitoring study, sponsored by the Chemical Manufacturers Association and designed in cooperation with the Environmental Protection Agency (EPA), measured the levels of nonylphenol (NP) and its ethoxylates (NPE) in 30 rivers. The sites, all receiving municipal or industrial wastewater, were selected at random from EPA’s United States river reach database by a statistical procedure. Water column and bottom sediment samples were collected along a perpendicular transect at each site. All samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
209
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(226 citation statements)
references
References 9 publications
10
209
3
2
Order By: Relevance
“…Compared with the other aquatic surface sediments (Fig. 3), the concentrations of total APs in this study are generally higher than most of those reported for other areas of the world, and lower than those of the two samples in the Hamilton Harbor site, Canada [20][21][22][23][24][25][26][38][39][40][41][42][43][44][45]. High concentrations of APs were reported for other highly industrialized and urbanized areas, such as Hamilton Harbor of the Great Lakes (up to 72,000 ng/g dw of NP and 1800 ng/g dw of OP) [38], Virginia (USA) sediments adjacent to STPs and outfall (up to 14,100 ng/g dw) [23], and Jamaica Bay (NY, USA)(up to 13,700 ng/g dw of NP and 45 ng/g dw of OP) [25].…”
Section: Ap Contents By Soxhlet Extraction and Distributioncontrasting
confidence: 71%
“…Compared with the other aquatic surface sediments (Fig. 3), the concentrations of total APs in this study are generally higher than most of those reported for other areas of the world, and lower than those of the two samples in the Hamilton Harbor site, Canada [20][21][22][23][24][25][26][38][39][40][41][42][43][44][45]. High concentrations of APs were reported for other highly industrialized and urbanized areas, such as Hamilton Harbor of the Great Lakes (up to 72,000 ng/g dw of NP and 1800 ng/g dw of OP) [38], Virginia (USA) sediments adjacent to STPs and outfall (up to 14,100 ng/g dw) [23], and Jamaica Bay (NY, USA)(up to 13,700 ng/g dw of NP and 45 ng/g dw of OP) [25].…”
Section: Ap Contents By Soxhlet Extraction and Distributioncontrasting
confidence: 71%
“…They may also pose a potential environmental threat to aquatic organisms. Owing to the importance of sediments on the transport, fate and bioavailability of EDCs, investigations on the sediment contamination of EDCs have been widely carried out (Naylor et al, 1992;Hale et al, 2000;Isobe et al, 2001;Heemken et al, 2001;López de Alda et al, 2002;Jonkers et al, 2003;Rice et al, 2003;Li et al, 2004a,b;Patrolecco et al, 2004;Chen et al, 2006;Fu et al, 2007;Labadie et al, 2007), and phenolic xenoestrogens with high levels were reported worldwide. For example, the sedimentary concentrations of nonylphenol and octylphenol were up to 72,000 ng/g and 1800 ng/ g dw, respectively, from Hamilton Harbor of the Great Lakes, Canada, which was highly impacted by anthropogenic activities (Bennie et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Alkylphenol polyethoxylates with 8-12 ethoxylate groups are commonly used, with nonylphenol polyethoxylates accounting for about 80% of the total. It has been estimated that 60% of alkylphenol polyethoxylates end up in the aquatic environment, 21) most entering via sewage treatment works, where they are readily degraded to form relatively stable metabolites. 22,23) Some of these metabolites are hydrophobic (e.g.…”
mentioning
confidence: 99%